Space and Number: Two Ways in Ontology? - Rabouin, David (Filozofski vestnik, 2020)
In this paper, I pursue a dialogue initiated with the publication of Logiques des mondes on the basis of three main lines of questioning: 1. The first, most immediate one, is the meaning that should be given to the famous motto “mathematics = ontology”. Indeed, it is a different statement to claim that “mathematics is ontology”, as was promoted explicitely by Being and the event, and to say that set theory alone is ontology (as advanced by Logiques des mondes, as well as other contemporary texts). It seems that there is at this point an important inflection of the system, not thematized as such; is set theory a way of expressing ontology, i.e. mathematics, or is it ontology itself? 2. This leads to a broader questioning of the relationship, in mathematics, between expression and ontology, or “language” and “being”. Here I would like to point out that, contrary to what one might think, there is often an ambiguity between these two aspects not only in Badiou, but more generally in discussions of the philosophy of mathematics. If this distinction is relevant - and I will try to show why it should be - then one cannot conclude too quickly from the fact that mathematics has adopted a unified expression thanks to the language of set theory to the fact that the form of being it expresses is set-theoretic (or “pure multiple” in Badiou’s terminology); 3. Finally, I would like to delve into the fact that the set-theoretic language has precisely given rise to the thematization of two orientations which could be just as well coined “ontological” (but in a different sense, therefore, from that given to it by Badiou); the first is anchored in the concept of number, while the other is anchored in the concept space (later called “topological”). The fact that we have a language capable of describing them in a homogeneous fashion does not entail that we are dealing with a single domain of objects. I would like to show that this tension runs through contemporary mathematics, and consequently through Alain Badiou’s thinking more than he wants to admit. In fact, it is at the basis of various attempts proposed in mathematics to arrive at more satisfactory forms of unification than that provided by “sets” alone.